2017
DOI: 10.1136/bmjopen-2017-016499
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and acceptability of antidepressant treatment in poststroke depression: a multiple-treatments meta-analysis

Abstract: ObjectiveThe aim of this study is to create a rank order of the comparative efficacy and acceptability (risk of all-cause discontinuation) of antidepressant treatment in poststroke depression (PSD) by integrating direct and indirect evidence.DesignMultiple-treatments meta-analysis of randomised controlled trials.ParticipantsPatients with depression following stroke.Interventions10 antidepressants and placebo in the acute treatment of PSD.Outcome measuresThe primary outcomes were the overall efficacy, defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 48 publications
2
20
1
5
Order By: Relevance
“…Previous systematic studies have addressed this topic to evaluate the efficacy of paroxetine for the treatment of patients with PSD. [ 16 18 ] However, they drew inconsistent conclusions based on their results. One study designed with multiple treatments by meta-analysis of randomized controlled trials to create a rank order of the comparative efficacy and acceptability of different medications in PSD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous systematic studies have addressed this topic to evaluate the efficacy of paroxetine for the treatment of patients with PSD. [ 16 18 ] However, they drew inconsistent conclusions based on their results. One study designed with multiple treatments by meta-analysis of randomized controlled trials to create a rank order of the comparative efficacy and acceptability of different medications in PSD.…”
Section: Discussionmentioning
confidence: 99%
“…One study designed with multiple treatments by meta-analysis of randomized controlled trials to create a rank order of the comparative efficacy and acceptability of different medications in PSD. [ 16 ] It found that paroxetine might be the best option for treating PSD after acute stroke, and fluoxetine might be the worst option. On the other hand, the other Cochrane systematic review failed to draw a positive conclusion of pharmacological agents, including paroxetine, and psychological therapies, because of the insufficient evidence.…”
Section: Discussionmentioning
confidence: 99%
“…94 Another network meta-analysis found doxepin, paroxetine, and nortriptyline to be significantly more effective than placebo, with paroxetine appearing to demonstrate the best balance between efficacy, acceptability, and tolerability, 95 a finding echoed by another meta-analysis. 96 A 2018 meta-analysis found sertraline to be associated with improvements in depressive symptoms as well as functional ability and neurologic deficits, though the effect disappeared when low-quality studies were excluded. 97 In one study, the serotonin and norepinephrine reuptake inhibitor (SNRI) duloxetine outperformed sertraline and citalopram for depressive symptom reduction at 4-and 8-week follow-up but not at the 12-week endpoint, suggesting a potential advantage for duloxetine in rapid symptom reduction.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Similar to psychotherapeutic interventions, antidepressants with efficacy in the general population have demonstrated efficacy in the medically ill, but with fewer supporting studies, smaller samples sizes and lower antidepressant effect sizes (Kennedy et al, 2016;Ostuzzi et al, 2018). Metaanalytic level data has demonstrated small-to-moderate antidepressant effect sizes of antidepressants for MDD in cancer (Ostuzzi et al, 2018), diabetes (Baumeister et al, 2014;Darwish et al, 2018), coronary heart disease (Ostuzzi et al, 2019), post-stroke (Robinson and Jorge, 2016;Sun et al, 2017), HIV (Eshun- Wilson et al, 2018), epilepsy (Elger et al, 2017;Maguire et al, 2014) and MS (Fiest et al, 2016). The benefits of antidepressants in heart failure and major neurocognitive disorder are unclear with mixed results (Das et al, 2019;Dudas et al, 2018).…”
Section: Pharmacological Interventions In the Medically Illmentioning
confidence: 99%